Isolasi dan Identifikasi Bakteri Gram Negatif Pada Luka Ikan Maskoki (Carassius auratus) Akibat Infestasi Ektoparasit Argulus sp. [Isolation and Identification Gram Negative Bacteria At Lessions Of Gold Fish (Carassius auratus) By Infestation Ectoparasite Argulus sp. - Kismiyati Kismiyati; Sri Subekti; R. Wahid Nur Yusuf; Rahayu Kusdarwati (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractOne of them is the problem of disease Argulus sp. is ektoparasite which often attacked in activity of good conducting of sea water and also freshwater. Argulus sp. attacking at part of fin, husk, gill and entire all its body exterior of him. attacked by fish is Argulus sp. will seen is thin, often rub body and arise red pock which later can generate secondary infection. Utilize to prove the existence of bacterium which emerge effect of lession (secondary infection) which because of bite of Argulus sp. that is by identifying bacterium and biochemical test. Media which used in identifying bacterium for example that is TSA (Tryptic Soy Agar), TSIA (Triple Soy Iron Agar), MIO (Motility Indol Ornithin), O/F medium (Oksidative/Fermentative), sugar test medium (maltosa, laktosa, arabinosa, inositol, manitol, sukrosa). Target of this research is to know the existence of gram negative bacterium and gram negative bacterium any kind of which is found at fish hurt of gold fish (Carassius auratus) effect of infestation by ectoparasite Argulus sp. Research which is use descriptive method. That is with infestation of Argulus sp. into containing aquarium of gold fish counted 1 tail and Argulus sp. counted 5, 10, 15, 20 tail. After Argulus sp. patch all at gold fish is later then perceived until gold fish arise lession effect of bite of Argulus sp. is afterwards identifyed by bacterium to know the bacterium that were formed on gold fish lesions. The result showed that the lesions of gold fish, isolation at TSA medium and identified by biochemical test to diagnose bacteriums found on gold fish lession. Identifications of the three gram negative bacterium as follow : Aeromonas hydrophilla, Pseudomonas flourescens, Flexibacter columnaris while for the Edwardsiella tarda was not be found in this study